Resiliencia y rendimiento académico en un niño con discapacidad intelectual leve - Zapata Armijos Paula Belén; Lozano Cabrera Tanya Karely (Machala, 2022)
The intellectual disability is hard one that is shown in the first schooling years, it remains in a person’s lifetime and it might bring about many personal and social troubles. This difficult affects not only in teaching and learning process but also the emotional status of a child. Because of that the resilience is a fundamental characteristic in every person and it is more important if is about students with some educative necessity related or not to a disability because they require of this factor that benefit them más allows to reach their academic achievements. With respect to the significant relationship that exists between the categories of analysis of the research, the following question arises: What is the relationship between resilience and academic performance in a child with mild intellectual disability? Therefore, the main purpose of this case study is to determine the relationship between resilience and academic performance of a child with mild intellectual disability, derived, evaluated and diagnosed in the District Unit of Support for Inclusion UDAI of the city of Machala. Regarding the methodology for the execution of this research, the case study method was used, of descriptive type and assuming the qualitative approach, after determining the methodology of this research, instruments were developed and applied according to the processing of the information obtained, among them are the interview, observation guide, documentaries, the school resilience scale (ERE) that allowed measuring the level of resilience in a child of 9 years of age and finally the Raven's intelligence test based on figures to assess the intellectual ability of the child, observation guide, documentaries, the school resilience scale (ERE) that allowed measuring the level of resilience in a 9 year old child and finally the Raven's intelligence test based on figures to evaluate the intellectual ability, problem solving and the capacity of logical and abstract reasoning in a person. These instruments and techniques served as the basis for the qualitative analysis of the research variables, from which the appropriate conclusions and recommendations were obtained. In conclusion, after analyzing the results achieved by comparing the variables, it has been shown that there is a positive correlation between some personal, social and school factors regarding the level of resilience and the child's academic performance, showing significant characteristics of optimism and dedication to learning, so that it is possible for the child to have an appropriate academic response. It should be emphasized that, according to the research design, it is intended to provide information that facilitates the work of teachers and families, providing concrete and real data that allow decision making to meet the needs of children with mild intellectual disabilities. Likewise, as part of the recommendations used for people with mild intellectual disabilities are, to actively involve families in the distribution of their education and upbringing, to provide an environment of security and attachment that provide children with solid foundations for their growth and development, taking into account the importance of strengthening the level of resilience, self-esteem and confidence in people with intellectual disabilities, since this will allow creating support networks with those around them.
La discapacidad intelectual es una dificultad que se evidencia en los primeros años de escolaridad, misma que perdura a lo largo de la vida de la persona y puede traer consigo muchos problemas tanto personales como sociales. Esta dificultad no solo afecta el proceso de enseñanza aprendizaje si no también el estado emocional del infante, por tal razón la resiliencia es una característica fundamental en cada sujeto y más aún si se trata de estudiantes con alguna necesidad educativa asociada o no a una discapacidad, requiriendo de este factor que los beneficia y les permite alcanzar sus logros académicos. Con respecto a la relación significativa que existe entre las categorías de análisis de la investigación, se plantea la siguiente problemática ¿Qué relación existe entre la resiliencia y el rendimiento académico en un niño con discapacidad intelectual leve? Por ende, el presente estudio de caso tiene como propósito primordial, determinar la relación existente entre la resiliencia y el rendimiento académico de un niño con discapacidad intelectual leve, derivado, evaluado y diagnosticado en la Unidad Distrital de Apoyo a la Inclusión UDAI de la Ciudad de Machala. En cuanto a la metodología para la ejecución de esta investigación se utilizó el método de estudio de caso, de tipo descriptivo y asumiendo el enfoque cualitativo, luego de determinar la metodología de dicha investigación se elaboraron y aplicaron instrumentos acordes para el procesamiento de la información obtenida, entre ellos están la entrevista, guía de observación, documentales, la escala de resiliencia escolar (ERE) que permitió medir el nivel de resiliencia en un niño de 9 años y por último el test de inteligencia de Raven basado en figuras para evaluar la habilidad intelectual, resolución de problemas y la capacidad de razonamiento lógico y abstracto en una persona. Estos instrumentos y técnicas sirvieron como base para ejecutar el análisis cualitativo de las variables de investigación, de las cuales se obtuvieron las conclusiones y recomendaciones oportunas. En conclusión, después de analizar los resultados alcanzados mediante la comparación de las variables, se ha demostrado que existe una correlación positiva entre algunos factores personales, sociales y escolares en cuanto al nivel de resiliencia y el rendimiento académico del niño, evidenciando características significativas de optimismo y dedicación a su aprendizaje, de modo que le es posible tener una respuesta académica apropiada. Cabe recalcar que, en función de lo diseñado en la investigación, se pretende proporcionar información que facilite la labor docente y familiar, brindando datos concretos y reales que permitan la toma de decisiones ante las necesidades que presenten los niños con discapacidad intelectual leve. Asimismo, como parte de las recomendaciones empleadas para personas con discapacidad intelectual leve están, efectuar la participación activa de las familias en la distribución de su educación y crianza, proveer un ambiente de seguridad y apego que proporcionen a los niños bases sólidas para su crecimiento y desarrollo, teniendo en cuenta la importancia de reforzar el nivel de resiliencia, autoestima y confianza en personas con discapacidad intelectual, puesto que esto permitirá crear redes de apoyo con quienes los rodean.
Keywords: DISCAPACIDAD INTELECTUAL; RESILIENCIA; RENDIMIENTO ACADEMICO; ENSEÑANZA-APRENDIZAJE